(3JMaI Chdj GdCdHGH aj UfGYI GdNW hGdcJGHs - (3YHO GdQMef Hf jhSa, GHf GdUGFZ,J (B845 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj Yde HGdbde Yde GdEfSGf eG de jYde bGd JYGdi (B: "(3GbQC hQHc GdCcQe GdPj Yde HGdbde Yde GdEfSGf(B" s
(3BNQgG (B:s
(3hGdOGd GdebdhHI EPG cGf eaQOkG CVjb ef GdjGA GdoeQcHI hgPG eG hLO ef LeY GdTjN GHf GdUGFZ JeJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B243s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JYdje JjehQ (B19) s
Keywords: (3GdNW hCdGJgs